Acne and risk of mental disorders: A two-sample Mendelian randomization study based on large genome-wide association data - Liu, Lin; Xue, Yuzhou; Chen, Yangmei; Chen, Tingqiao; Zhong, Judan; Shao, Xinyi; Chen, Jin (Frontiers in Public Health, 2023)
Background: Despite a growing body of evidence that acne impacts mental disorders, the actual causality has not been established for the possible presence of recall bias and confounders in observational studies. Methods: We performed a two-sample Mendelian randomization (MR) analysis to evaluate the effect of acne on the risk of six common mental disorders, i.e., depression, anxiety, schizophrenia, obsessive-compulsive disorder (OCD), bipolar disorder, and post-traumatic stress disorder (PTSD). We acquired genetic instruments for assessing acne from the largest genome-wide association study (GWAS) of acne (N = 615,396) and collected summary statistics from the largest available GWAS for depression (N = 500,199), anxiety (N = 17,310), schizophrenia (N = 130,644), OCD (N = 9,725), bipolar disorder (N = 413,466), and PTSD (N = 174,659). Next, we performed the two-sample MR analysis using four methods: inverse-variance weighted method, MR-Egger, weighted median, and MR pleiotropy residual sum and outliers. Sensitivity analysis was also performed for heterogeneity and pleiotropy tests. Results: There was no evidence of a causal impact of acne on the risk of depression [odds ratio (OR): 1.002, P = 0.874], anxiety (OR: 0.961, P = 0.49), OCD (OR: 0.979, P = 0.741), bipolar disorder (OR: 0.972, P = 0.261), and PTSD (OR: 1.054, P = 0.069). Moreover, a mild protective effect of acne against schizophrenia was observed (OR: 0.944; P = 0.033). Conclusion: The increased prevalence of mental disorders observed in patients with acne in clinical practice was caused by modifiable factors, and was not a direct outcome of acne. Therefore, strategies targeting the elimination of potential factors and minimization of the occurrence of adverse mental events in acne should be implemented.